2017
DOI: 10.1371/journal.pone.0181761
|View full text |Cite
|
Sign up to set email alerts
|

The integrated analysis of RNA-seq and microRNA-seq depicts miRNA-mRNA networks involved in Japanese flounder (Paralichthys olivaceus) albinism

Abstract: Albinism, a phenomenon characterized by pigmentation deficiency on the ocular side of Japanese flounder (Paralichthys olivaceus), has caused significant damage. Limited mRNA and microRNA (miRNA) information is available on fish pigmentation deficiency. In this study, a high-throughput sequencing strategy was employed to identify the mRNA and miRNAs involved in P. olivaceus albinism. Based on P. olivaceus genome, RNA-seq identified 21,787 know genes and 711 new genes by transcripts assembly. Of those, 235 genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Furthermore, at least 84% of the clean reads from each library were mapped on to the genome of the olive flounder, which is higher than what has been previously reported. Previous reports have shown that the mapping rates were only 67.32, 74, and 79.13% ( 18 , 27 ), which are relatively low. It has been speculated that the low mapping rates of olive flounders may be due to their imperfect reference genome ( 18 ).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Furthermore, at least 84% of the clean reads from each library were mapped on to the genome of the olive flounder, which is higher than what has been previously reported. Previous reports have shown that the mapping rates were only 67.32, 74, and 79.13% ( 18 , 27 ), which are relatively low. It has been speculated that the low mapping rates of olive flounders may be due to their imperfect reference genome ( 18 ).…”
Section: Discussionmentioning
confidence: 75%
“…In recent years, ceRNA regulatory networks have been widely investigated in types of diseases (11,37). Moreover, Chu et al (27,38) confirmed the hypothesis that ceRNA regulatory networks also exist in teleosts. In this study, the lncRNA-miRNA-mRNA networks were constructed by using a combination of lncRNA-miRNA and miRNA-mRNA pairs.…”
Section: Lncrna-mirna-mrna Network In Olive Floundermentioning
confidence: 89%
See 1 more Smart Citation
“…By assessing mRNA profiles, it is possible to interrogate the specific genetic processes underlying, and giving rise to, specific phenotypes of interest. The use of transcriptomics has expanded to evaluate the transcriptional profile of other RNA populations [ 4 ], such as rRNAs [ 5 ], miRNAs [ 6 8 ], tRNAs [ 9 , 10 ], and other small RNAs [ 11 14 ]. Traditional transcriptomics analyses usually identify transcriptional alterations in a single organism.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic platforms have been successfully applied to understand diverse molecular and physiological characteristics of P . olivaceus [ 11 14 ]. The recently published whole genome sequence of P .…”
Section: Introductionmentioning
confidence: 99%